Design Aplications To Increase Relevance To Search Thesis (A Case Study In Institute of Business and Information Stikom Surabaya Library) - Wahyudi, Ikhsan Pratama; Wurijanto, Tutut; Sulistiowati, Sulistiowati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
The library is a vital part of an educational institution like university, especially for the Institute of Business and Information Stikom Surabaya. The availability of the final task collection became the main reason users to use library facilities. But handling in the search collections not implement the concept of Information Retrieval yet. Information retrieval used to produce information or documents which relevant to keyword from source by the amount that are numerous and is not structured as a collection of final task literatures .To solve these problems, the necessary repairs final task search facility by implementing the concept of Information Retrieval. The application of Information Retrieval on an abstract document is expected to produce a collection of  final task literatures which is relevant to the search. From the testing, the application capable of producing the collection of final tasks more than by search through query when given keywords with combination affix (prefix and  suffix).